Economic Impact of Major Sporting Events: A Case Study of the Olympic Games - Dr. Gaurav Singh; Dr. Kavya Krishnan (CINEFORUM, 2024)
It has been widely acknowledged for a long time that major athletic events, such as the Olympic Games, serve as a spur for economic growth and development in the nations and cities that host, respectively. It is common for the draw of hosting big events to transcend beyond the sphere of athletics, as it promises huge economic advantages, increased tourism, and better worldwide awareness. to shed light on both the benefits and the problems that are connected with these mega-events, a complete case study that closely explores the economic effect of hosting the Olympic Games is presented here. an examination of the historical setting of important athletic events, including a trace of the development of the Olympic Games from ancient Greece to the contemporary, international spectacle that they have become. Following that, we will begin on a voyage around the economic environment, during which we will conduct an analysis of the elements that contribute to the unrealistically high expectations of economic windfalls that are connected with hosting the Olympics